2011
DOI: 10.1111/j.1442-200x.2011.03340.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypospadias in Istanbul: Incidence and risk factors

Abstract: Genetic predisposition and placental insufficiency in early gestation might play a role in the etiology of hypospadias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 49 publications
(294 reference statements)
3
20
0
3
Order By: Relevance
“…The most common associated anomalies in boys with hypospadias are cryptorchidism and inguinal hernia, present in about 8%–10% and 9%–15% of these patients, respectively 24. In addition, 17.6% of hypospadiac boys in Istanbul were found to have malformations of the genital or inguinal region 25. Our results were in good agreement with these previous findings.…”
Section: Discussionsupporting
confidence: 92%
“…The most common associated anomalies in boys with hypospadias are cryptorchidism and inguinal hernia, present in about 8%–10% and 9%–15% of these patients, respectively 24. In addition, 17.6% of hypospadiac boys in Istanbul were found to have malformations of the genital or inguinal region 25. Our results were in good agreement with these previous findings.…”
Section: Discussionsupporting
confidence: 92%
“…Akin et al [19] observed positive family history in patients with hypospadias in 26.5% cases in their study in Turkey. Abdelrahman et al [20] also observed 12% hypospadias patients with positive family history for this condition.…”
Section: Discussionmentioning
confidence: 87%
“…In contrast to 2.8% patients with hypospadias associated with cryptorchidism, Akin et al [19] reported 14.7% patients of hypospadias with cryptorchidism. Abdelrahman et al [20] observed this positive relationship between hypospadias and cryptorchidism in 20%.…”
Section: Discussionmentioning
confidence: 99%
“…İngiltere'de 1993 ile 2000 yılları arasında 3.1/1000 oranında iken, Quebec, Kanada'da 11.4/1000 sıklıkta görülmüştür (19,20) . Ülkemizde İstanbul'da yapılan bir çalışmada, bu oran 19.4/1000 olarak saptanmıştır (21) . Yine de tanı koymada ve veri analizindeki farklılıklar bu konuda yorum yapmayı güçleştirmektedir.…”
Section: üRetra Ve Hipospadiasunclassified